Boron‐Based Multi‐Resonance TADF Emitter with Suppressed Intermolecular Interaction and Isomer Formation for Efficient Pure Blue OLEDs (Small 19/2022). Issue 19 (12th May 2022) - Cheon, Hyung Jin; Shin, Youn‐Seob; Park, Noh‐Hwal; Lee, Jeong‐Hwan; Kim, Yun‐Hi
Abstract : Pure Blue Organic Light‐Emitting Diodes In article number 2107574, Jeong‐Hwan Lee, Yun‐Hi Kim, and co‐workers use a strategic substitution of the bulky groups to effectively suppress the intermolecular interaction and the formation of isomers in mBP‐DABNA‐Me. Therefore, the mBP‐DABNA‐Me–based organic light‐emitting diode exhibits an efficiency of 24.3% with a pure blue emission, color‐coordinate of (0.124, 0.140). Notably, the substituents hinder the bathochromic shift, keeping the pure blue emission even at a high concentration of 25%.